Give Them Vasculature and Immune Cells: How to Fill the Gap of Organoids - Yip, Sophronia; Wang, Nan; Sugimura, Ryohichi (Cells, tissues, organs, 2023)
Valid and relevant models are critical for research to have biological relevance or to proceed in the right path. As well-established two-dimensional cell cultures lack niches and cues and rodent models differ in species, three-dimensional organoids emerged as a powerful platform for research. Cultured in vitro from stem cells, organoids are heterogeneous in cells and closely resemble the in vivo settings. Organoids also recapitulate the unique human features if cultured from a human source and are subjected to genetic modification. However, one type of organoid possesses only a limited selection of cells. In particular, the absence of vasculature and immune cells restricts the organoids from nutrition, cues, or critical interactions, undermining the validity of organoids as physiological or pathological models. To fill the current gap, there is an urgent need to provide organoids with vasculature and immune cells. In this paper, we review the methods to generate physiological and pathological organoid models and summarize ways to vascularize or immunize them. Our discussion continues with some advantages and disadvantages of each method and some emerging solutions to current problems.